Cost-effectiveness analysis of domestic 13-valent pneumococcal conjugate vaccine for children under 5 years of age in mainland China. Issue 7 (3rd July 2021) - Wang, Caixia; Su, Li; Mu, Qiuling; Gu, Xueyan; Guo, Xuejun; Wang, Xuxia
ABSTRACT: Background : The first Chinese domestic 13-valent pneumococcal conjugate vaccine (WoAnxin®, PCV-13) is available for children aged 2 months to 5 years and is more economical than import vaccine with equal safety and immunogenicity. However, the cost-effectiveness of this new PCV-13 for children <5 years in mainland China is not clear. Methods : In the present study, we developed a Markov model under societal perspective to evaluate the incremental cost-effectiveness ratios (ICERs) of five birth cohorts of 100, 000 Chinese infants across four alternative vaccination programs:1) no vaccination; 2) vaccinate 4 doses of new PCV-13 for children aged 2 to 6 months; 3) vaccinate 3 doses of new PCV-13 for children aged 7 to 11 months; 4) vaccinate 2 doses of new PCV-13 for children aged 12 to 23 months; 5) vaccinate 1 dose of new PCV-13 for children aged 2 to 5 years. We conducted one-way and probability sensitivity analysis to determine the uncertainty of the model findings. Results : We found that with awillingness-to-pay (WTP) threshold of three-times Chinese per-capita gross domestic product (GDP) all vaccination programs were cost-effective compared to no vaccination and children aged 2 to 5 years received 1 dose of new PCV-13 would incur the lowest additional cost of US$2417 per quality-adjusted-life-years (QALYs) compare with other vaccination programs ($15394/QALYs for 4 doses program, $9292/QALYs for 3 doses program, $4445/QALYs for 2 doses program). Conclusions : According to our results, China should give priority to incorporating new PCV-13 into its national immunization program.